Influence of Added Cellulose Nanocrystals on the Rheology of Polymers - Rajinder Pal; Parth Deshpande; Smit Patel (Nanomaterials)
The interactions between cellulose nanocrystals and six different polymers (three anionic, two non-ionic, and one cationic) were investigated using rheological measurements of aqueous solutions of nanocrystals and polymers. The experimental viscosity data could be described adequately by a power-law model. The variations in power-law parameters (consistency index and flow behavior index) with concentrations of nanocrystals and polymers were determined for different combinations of nanocrystals and polymers. The interactions between nanocrystals and the following polymers: anionic sodium carboxymethyl cellulose and non-ionic guar gum, were found to be strong in that the consistency index increased substantially with the addition of nanocrystals to polymer solutions. The interaction between nanocrystals and non-ionic polymer polyethylene oxide was moderate. Depending on the concentrations of nanocrystals and polymer, the consistency index both increased and decreased upon the addition of nanocrystals to polymer solution. The interactions between nanocrystals and the following polymers: anionic xanthan gum, anionic polyacrylamide, and cationic quaternary ammonium salt of hydroxyethyl cellulose, were found to be weak. The changes in rheological properties with nanocrystal addition to these polymer solutions were found to be small or negligible.